2020
DOI: 10.1007/s42978-020-00084-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cardiorespiratory and Metabolic Responses Between Kettlebell Half Marathon and Treadmill Running at the Same Average Oxygen Consumption: A Case Study

Abstract: Purposes In kettlebell sport (KS) half marathon, the lift of the kettlebell is required for the highest number of repetitions in 30 min. No data are available on cardiorespiratory and metabolic responses during this exercise routine. The aim of the study was to evaluate cardiopulmonary and metabolic responses to KS half marathon compared to 30 min treadmill running, chosen as a reference paradigm of aerobic exercise, at the same average oxygen consumption (VO2). Methods A male elite KS athlete was enrolled i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
1
0
1
Order By: Relevance
“…The VO 2max mirrors the maximum amount of oxygen an individual can use to support the oxidative production of energy [6]. The most common and reliable method to assess VO 2max is the cardiopulmonary exercise test, recognized a valuable measure not only to assess the functional status and oxygen availability during exercise training but also to discriminate cardiorespiratory, pulmonary and musculoskeletal function at the same average oxygen consumption [7]. For the first time, Alvarez et al [8] showed that high values of VO 2max were essential for futsal athletes at the professional level, suggesting the relevance of aerobic power in futsal [8].…”
Section: Introductionmentioning
confidence: 99%
“…The VO 2max mirrors the maximum amount of oxygen an individual can use to support the oxidative production of energy [6]. The most common and reliable method to assess VO 2max is the cardiopulmonary exercise test, recognized a valuable measure not only to assess the functional status and oxygen availability during exercise training but also to discriminate cardiorespiratory, pulmonary and musculoskeletal function at the same average oxygen consumption [7]. For the first time, Alvarez et al [8] showed that high values of VO 2max were essential for futsal athletes at the professional level, suggesting the relevance of aerobic power in futsal [8].…”
Section: Introductionmentioning
confidence: 99%
“…В настоящее время в области гиревого спорта ученых интересуют количественные показатели потребления кислорода (V O2 ) и частоты сердечных сокращений (ЧСС) при интенсивных упражнениях с гирями в сравнении с такими же показателями в других видах спорта [3]. Например, обнаружено, что упражнения с гирями вызывают гораздо более высокую сердечно-легочную и метаболическую реакцию, чем бег на беговой дорожке, выполняемый с аналогичным уровнем V O2 [4]. Небольшое количество работ посвящено определению способов дыхания в упражнениях с гирями по видеоматериалам, где количество дыхательных циклов определяется по характерным для дыхания движениям груди, живота и лопаток [5].…”
unclassified